Parametrization and validation of a tool for the electrical design of tubular redox flow stacks - Fabian Brandes and Antonio Chica Lara and Thorsten Struckmann (Swanbarton Limited, 2023)
All-vanadium redox flow batteries (VRFB) with a tubular cell geometry offer advantages over the common planar design: improved stability, reduced sealing lengths, cost-saving potentials through production of the components by (co-)extrusion and a more flexible electric cell-setup, possibly reducing shunt currents. In prior works a tubular cell design for VRFBs was developed and further improved by our research group. To transfer the single cell performance to industrial levels, a design tool for stacks suited to the tubular cell geometry is necessary. We report on the progress of parametrisation and validation of the design tool.